The Interchangeable Worker and Fighting Back: Identifying Some Strategic Issues - Reiter, Ester (Labour/Le Travailleur, 1988)
Abstract Organizing unorganized workers, particularly the growing number of women and young people in part-time jobs, is one of the major challenges for organized labour. The restructuring of the restaurant industry in the post-World War II period produced a work situation in which traditional workplace organizing strategies were rendered ineffective. This paper explores the development of the interchangeable worker in the fast food sector of the industry and examines how a feminist approach to work, which stresses the links between paid work, family, and community, is a more appropriate model upon which to develop suitable strategies for dealing with this increasingly common workplace.